Indignidade e deserdação - Torrano, Luiz Antônio Alves (2012)
In the light of the current code, other relevant laws, and notwithstanding the classical doctrine, the aim of the present work is to set the limits and consequences of the institution of the unworthiness and disinheritance, with which, far from any disregard to ancient teachings, a new approach demanded by the social vision that one must have nowadays must be given. Hence, this work is divided into chapters, in which, since the very beginning, one studies the historical aspects of the legal succession, the indignity and the disinheritance in the country‟s doctrine and the alien legal compilation, from which a new appraisal regarding the concept and the legal nature of these institutions is derived, leaving out the doctrine that foresees them as a civil sanction, or even as an inability to have them as mere absence of legitimacy to inherit or receive some legacy. Moreover, their similarities and differences, the causes that attempt the exclusion of succession as well as their effects which in some cases come from the new family law that grants marriage and homosexual affective stable unions are pointed out. Afterwards, the destination of the inheritance properties and the acts performed by those excluded are also considered in this work. In the study of the necessary exclusion, apart from discussing the active and passive legitimacy; implicit or explicit forgiveness given by the legatee to the successor is also focused on, as well as the prescription of the intention to exclude the heir or the inheritor